Caribbean Court of Justice : a developmental tool - Nicholson, A. J. (2003)
Considers the main elements of the debate concerning the Privy Council and the Caribbean Court of Justice. Reviews where Caribbean states have reached in the establishment of the Caribbean Court of Justice. Looks at the main areas in which the Court will serve the development needs of the region as a whole.\n